2014
DOI: 10.3389/fendo.2014.00155
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAcylation, an Epigenetic Mark. Focus on the Histone Code, TET Family Proteins, and Polycomb Group Proteins

Abstract: There are increasing evidences that dietary components and metabolic disorders affect gene expression through epigenetic mechanisms. These observations support the notion that epigenetic reprograming-linked nutrition is connected to the etiology of metabolic diseases and cancer. During the last 5 years, accumulating data revealed that the nutrient-sensing O-GlcNAc glycosylation (O-GlcNAcylation) may be pivotal in the modulation of chromatin remodeling and in the regulation of gene expression by being part of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 52 publications
1
58
0
Order By: Relevance
“…As UDP-GlcNAc is produced by the nutrient-dependent hexosamine biosynthetic pathway (Hart et al 2011), it has been suggested that O-GlcNAcylation by the OGT:UDP-GlcNAc complex serves as a nutrient sensor to regulate such processes as gene expression (see Dehennaut et al 2014).…”
mentioning
confidence: 99%
“…As UDP-GlcNAc is produced by the nutrient-dependent hexosamine biosynthetic pathway (Hart et al 2011), it has been suggested that O-GlcNAcylation by the OGT:UDP-GlcNAc complex serves as a nutrient sensor to regulate such processes as gene expression (see Dehennaut et al 2014).…”
mentioning
confidence: 99%
“…As nutrient transfer in the placenta from maternal sources to the developing fetus is of paramount importance, placental OGT affectively serves as a molecular “canary in a coal mine”, sensing changes in maternal energy and altering placental signaling to ultimately impact fetal programing. Recently, OGT’s domain has been expanded to epigenetics with the discovery that O-GlcNAclyation regulates several critical epigenetic links, including DNA demethylases and histone marks (reviewed by Dehennaut, Leprince, & Lefebvre, 2014). …”
Section: Ogt: a Transceiver Of Nutrient Signalsmentioning
confidence: 99%
“…These eight PPL-associatedmethylation sites, also correlated with fasting TG, account for a substantially greater amount of phenotypic variance (14.9%) in PPL and fasting TG (16.3%) when compared with the genetic contribution of loci identified by a previous GWAS (4.5%). In summary, the epigenomeis a large contributor to the variation in PPL, and this has the potential to be used to modulate PPL and reduce CVD [3,6,[13][14][15].…”
Section: An Omics Systems Approach: Genetic-epigenetic and Metabolomimentioning
confidence: 99%